Analysis of search behaviour in the NTU OPAC. - Lau, Eng Pwey. (2008)
This dissertation analyses the transaction logs of the NTU OPAC system to uncover interesting usage patterns of its users. The results indicate that a high proportion of NTU OPAC users are “Novices” who apply longer query lengths, limited use of Boolean operators and perform more consecutive queries than “Experts”.